14.9k views
2 votes
Help me anyone pleaseeee

Help me anyone pleaseeee-example-1
User Marianosz
by
5.7k points

1 Answer

2 votes
Answer: Choice A
a_n = 7 + (n-1)*(-4)

======================================
Step-by-step explanation:

The given set of equations tell you two things

* The first term is 7 because a_1 = 7. When I write "a_1", I mean "a subscript 1" where the 1 is smaller and to the right and slightly below 'a'. This will apply with a_n and a_(n-1) as well.

* The nth term a_n is found by subtracting 4 from the previous term a_(n-1). So the common difference is d = -4

So,
a_n = a_1 + d*(n-1)
a_n = 7 + (-4)*(n-1)
a_n = 7 + (n-1)*(-4)
which is choice A
User LightStruk
by
6.1k points